2023
DOI: 10.1038/s41598-023-34057-3
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid GWO-PSO based optimal placement and sizing of multiple PV-DG units for power loss reduction and voltage profile improvement

Abstract: Distributed generation (DG) is integrated in a passive distribution system to reduce power loss, improve voltage profile, and increase power output. To reap the most benefits of the distribution system, the best location and appropriate DG size must be determined. This paper presents a hybrid Grey wolf Optimizer (GWO) and Particle swarm optimization (PSO) approach for determining the best placement and DG size while considering a multi-objective function that includes active and reactive power loss minimizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The initial guess has a large effect on the convergence time. However, the method has a poor convergence characteristic [8,[13][14][15][16].…”
Section: Gauss Seidel Methodsmentioning
confidence: 99%
“…The initial guess has a large effect on the convergence time. However, the method has a poor convergence characteristic [8,[13][14][15][16].…”
Section: Gauss Seidel Methodsmentioning
confidence: 99%
“…For rapid radiation changes, it performs poorly, and the method's sophistication will continuously rise [ 12 ]. To regulate the power, this technique modifies the duty ratio slightly [ 13 ].…”
Section: Existing Tracking Techniquesmentioning
confidence: 99%
“…The papers in Refs. [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ], discuss the most popular methods.…”
Section: Introductionmentioning
confidence: 99%
“…The results presented through the arithmetic optimization algorithm (AOA) indicated that specific locations and sizes for multiple DG units delivering active and reactive power can reduce active power loss, voltage deviation, and voltage stability indicator 24 . In 25 , a GWO and PSO approach for selecting the optimal location and sizing of three PV-DGs, that minimize losses and improve the voltage profile has been presented. In 26 , 27 , the influence of the optimal allocation of different DGs (with different active and reactive power capabilities) into the distribution network has been investigated, which has demonstrated that the DG injecting both real and reactive power has the best technical performance.…”
Section: Introductionmentioning
confidence: 99%